The art of cheating medical staff- Munchausen Syndrome by Proxy - Natalia Zarankiewicz; Martyna Zielińska; Katarzyna Kosz; Aleksandra Kuchnicka; Wojciech Siedlecki; Katarzyna Książek; Sylwia Mojsym-Korybska (Journal of Education, Health and Sport, 2019)
Background: Munchausen syndrome by proxy (MSBP) is a behavioral disorder in adults, that affects children. This phenomenon is also called a Medical Child Abuse or Caregiver-fabricated illness. Child becomes a victim of many unnecessary medical procedures without a commensurate disease. A mild form of this disorder is falsification of medical records and fabrication of medical evidences. Adults can also exaggerate existing symptoms of illness. The most harmful behavior is an intentional child abusing in order to cause symptoms of a disease. There are many difficulties in diagnosing this disorder and the following consequences for victims are devastating. For that reason MSBP is becoming a very dangerous medical problem. Material and methods: The analysis concerned publications in English and Polish language published in years 2013-2018, which were collected in the PubMed, Google Scholar and Medycyna Praktyczna. Particular attention was paid to articles presenting the problem of MSBP and to the role of medical staff in diagnosing this disorder. Results: Available data suggests that caregiver with MSBP is usually victim’s mother. Most commonly these women have others mental disorders. MSBP is very dangerous form of violence and it is proven that the mortality associated with this disorder reaches about 6-33%. It should be noted, that in addition to the obvious child’s physical injuries, abnormal relationships with caregiver cause long-term developmental damages. Conclusion: The role of medical staff in diagnosing MSBP is difficult, but also very important. Caregivers with MSBP seem to be solicitous and responsible. Their attitude can mislead the doctor. Pediatricians, while trying to diagnose a child, order many diagnostic tests. It may increase caregiver’s pathological behavior. Due to this fact, medical staff can unconsciously expose child to unnecessary medical procedures. Effective communication between health sectors and staff education can be a crucial element in MSBP diagnosing.